Operational lessons learned in conducting an international study on pharmacovigilance in pregnancy in resource-constrained settings: The WHO Global Vaccine safety Multi-Country collaboration project. (August 2022) - Sharan, Apoorva; Jahagirdar, Shubhashri; Stuurman, Anke L; Elango, Varalakshmi; Riera-Montes, Margarita; Kumar Kashyap, Neeraj; Kumar Arora, Narendra; Mathai, Mathews; Mangtani, Punam; Devlieger, Hugo; Anderson, Steven; Whitaker, Barbee; et al.
Highlights: The feasibility and utility of conducting a large multi-country sentinel-site based surveillance study was evaluated in the context of maternal immunization vigilance. Prospective observational surveillance was undertaken for seven adverse perinatal and neonatal outcomes across 21 sites in seven countries over a 12-month period May 2019 to August 2020. Implementation of this study across geographically diverse sites with differing levels of infrastructure, clinical and health-care utilization practices was affected by several challenges, including, time-consuming ethics and administrative approvals, limited clinical documentation, challenges in follow-up and outcome identification and poor internet connectivity. The onset of the COVID-19 pandemic during the active data collection phase of the study also affected study implementation, temporarily disrupting data collection and study monitoring at many sites. Use of electronic platforms for data collection and issue resolution and application of a quality assurance plan with frequent interaction between central and site study teams emerged as key facilitators for study operationalization. The operational lessons learned from our study provide valuable insights for future benefit-risk assessments of pregnancy interventions and further strengthening vaccine pharmacovigilance in low- and middle-income countries. Abstract: The WHO Global Vaccine Safety Multi-Country Collaboration study on safety in pregnancy aims to estimate the minimum detectable risk for selected perinatal and neonatal outcomes and assess the applicability of standardized case definitions for study outcomes and maternal immunization in low- and middle-income countries (LMICs). This paper documents the operational lessons learned from the study. A prospective observational study was conducted across 21 hospitals in seven countries. All births occurring at sites were screened to identify select perinatal and neonatal outcomes from May 2019 to August 2020. Up to 100 cases per outcome were recruited to assess the applicability of standardized case definitions. A multi-pronged study quality assurance plan was implemented. The impact of the COVID-19 pandemic on site functioning and project implementation was also assessed. Multi-layered ethics and administrative approvals, limited clinical documentation, difficulty in identifying outcomes requiring in-hospital follow-up, and poor quality internet connectivity emerged as important barriers to study implementation. Use of electronic platforms, application of a rigorous quality assurance plan with frequent interaction between the central and site teams helped improve data quality. The COVID-19 pandemic disrupted data collection for up to 6 weeks in some sites. Our study succeeded in establishing an international hospital-based surveillance network for evaluating perinatal and neonatal outcomes using common study protocol and procedures in geographically diverse sites with differing levels of infrastructure, clinical and health-utilization practices. The enhanced surveillance capacity of participating sites shall help support future pharmacovigilance efforts for pregnancy interventions.